Independent Curriculum Implementation in EFL Classrooms: Practical Stages - Oktaviani, Oktaviani; Asfihana, Raida (Institut Agama Islam Negeri Palopo, 2024)
Independent Curriculum has given a new nuance to the education system in Indonesia. There are several significant changes in the independent curriculum, which aims to achieve optimal curriculum standards. Thus, this research aims to find out the stages of implementing this independent curriculum in English as Foreign Language (EFL) classrooms. This research took a single case study design and was conducted at a boarding-based junior high school. The researchers observed learning activities and interviewed an English teacher and fifteen students from three different classes. Observation and interviews provided data on how to implement the independent curriculum in EFL classes, which is supported by interview results. The results showcased that the teacher applied three practical stages in implementing the independent curriculum, namely planning and preparation, learning enactment, and evaluation. These stages cover the application of diagnostic assessments, formative and summative assessments, and teacher’s emphasis on student-centered learning strategies and integration between differentiated learning and cooperative learning. The integration of these three phases forms the main basis for an in-depth understanding of the dynamics and effectiveness of curriculum-based independent learning in the context of this research.